Physicochemical Characterization of Ethoxylation Products of Fatty Acid Esters - Lukosek, Marek; Emmons-Burzyńska, Magdalena; Alejski, Krzysztof; Szwach, Iwona (Frontiers in Chemical Engineering, 2021)
The processes of direct ethoxylation of methyl and ethyl esters of unsaturated fatty acids have been described. Two different types of catalysts were employed in those tests: calcium-based catalyst and aluminum-magnesium-based catalyst. Compositions of the synthesized oxyethylates were analyzed with the use of the GC / FID, GC / MS, GPC and HPLC, HPLC / MS, MALDI methods. Comparative evaluation of the obtained products for both types of catalysts was run in terms of reaction by-products. Biodegradation tests of the oxyethylated products were carried out according to OECD guidelines and physical and chemical properties of oxyethylates were specified which affects the directions of their applications.